Recording medium and inkjet recording method

JP7631114B2Active Publication Date: 2025-02-18CANON KK
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021100465
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-22
Filing Date
2021-06-16
Publication Date
2025-02-18
Estimated Expiration
2041-06-16

Smart Images

  • Figure 0007631114000008
    Figure 0007631114000008
  • Figure 0007631114000001
    Figure 0007631114000001
  • Figure 0007631114000002
    Figure 0007631114000002
Patent Text Reader

Abstract

To provide a recording medium showing excellent water resistance which can be displayed outside, and in which beading is hard to occur and high-quality image can be recorded even in the case of using aqueous ink.SOLUTION: A recording medium having a substrate, an ink-receiving layer (1) and an ink-receiving layer (2)arranged on the outermost surface. The thickness of the ink-receiving layer (2) is 10 nm or more and 4,000 nm or less, the ink-receiving layer (1) contains first inorganic particles and a first binder, the ink-receiving layer (2) contains second inorganic particles and second binder, both the first binder and the second binder are water-insoluble resin, a contact angle θ1 of the surface of the ink-receiving layer (1) with water is 90° or more, and a contact angle θ2 of the surface the ink-receiving layer (2) with water is 60° or more and 85° or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a recording medium and an inkjet recording method. [Background technology]

[0002] In recent years, with the increase in the speed of image recording using a recording device such as an inkjet recording device, there is a demand for recording media capable of recording images with excellent image quality and color development. In addition, there are an increasing number of occasions where a recorded matter obtained by recording an image on a recording medium is displayed outdoors. When a recorded matter is displayed outdoors, the recorded matter may be laminated to protect the image from the effects of rain and wind. However, laminating a recorded matter makes the processing process complicated and increases costs. For this reason, in recent years, there has been a demand for recording media that are less affected by rain and wind and have improved water resistance even without lamination.

[0003] For example, recording media with a layer containing a water-insoluble resin such as an acrylic resin or a urethane resin have been proposed as recording media with improved water resistance for obtaining records for outdoor display (Patent Documents 1 to 4). Also, a recording sheet has been proposed in which an ink-permeable layer containing a surfactant with an HLB value of 9 or less is provided on an ink-receiving layer, thereby improving the ink absorption of the ink-receiving layer (Patent Document 5). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-105235 A [Patent Document 2] JP 2006-110787 A [Patent Document 3] JP 2006-051741 A [Patent Document 4] JP 2018-165053 A [Patent Document 5] JP 2002-002090 A Summary of the Invention [Problem to be solved by the invention]

[0005] The recording media proposed in Patent Documents 1 and 2 had a certain degree of improved water resistance by providing a layer containing a water-insoluble resin as the outermost layer, but did not exhibit the high level of water resistance required in recent years. On the other hand, the recording media proposed in Patent Documents 3 and 4 had improved water resistance in the ink receiving layer. However, it was found that when aqueous ink is applied to the ink receiving layer of these recording media, so-called beading is likely to occur, and the quality of the recorded image may be impaired.

[0006] Therefore, an object of the present invention is to provide a recording medium that exhibits excellent water resistance allowing for outdoor display, is less susceptible to beading even when using aqueous ink, and is capable of recording high-quality images.

[0007] In addition, it was found that when a polyester resin is used as a binder in the ink receiving layer constituting the recording sheet proposed in Patent Document 5, the polyester resin is easily hydrolyzed, resulting in a problem that the durability of the ink receiving layer is easily insufficient.

[0008] Therefore, another object of the present invention is to provide a recording medium having an ink-receiving layer excellent in ink absorbency and durability sufficient for outdoor display, and further, to provide an ink-jet recording method capable of recording high-quality images. [Means for solving the problem]

[0009] The above object is achieved by the present invention as described below. That is, according to the present invention, there is provided a recording medium having a substrate, an ink receiving layer (1) provided on the substrate, and an ink receiving layer (2) provided on the ink receiving layer (1) and disposed on the outermost surface, the thickness of the ink receiving layer (2) being 10 nm to 4,000 nm, the ink receiving layer (1) containing first inorganic particles and a first binder, the ink receiving layer (2) containing second inorganic particles and a second binder, both of the first binder and the second binder being water-insoluble resins, the contact angle θ1 of the surface of the ink receiving layer (1) with water one second after the surface of the ink receiving layer (1) is brought into contact with water is 90° or more, and the contact angle θ2 of the surface of the ink receiving layer (2) with water one second after the surface of the ink receiving layer (2) is brought into contact with water is 60° or more and 85° or less.

[0010] According to the present invention, there is also provided a recording medium having a substrate, an ink receiving layer (1) provided on the substrate, and an ink receiving layer (2) provided on the ink receiving layer (1) and disposed on the outermost surface thereof, the ink receiving layer (2) having a thickness of 10 nm to 4000 nm, the ink receiving layer (1) containing first inorganic particles and a first binder, the ink receiving layer (2) containing second inorganic particles and a second binder, and the first binder and the second binder. and the ink-receiving layer (2) are both water-insoluble resins, and the contact angle θA of the surface of the ink-receiving layer (2) with water 60 seconds after contacting the surface of the ink-receiving layer (2) with water is 40° or more and 80° or less, and the contact angle θA and the contact angle θA of the surface of the ink-receiving layer (2) with water 60 seconds after the recording medium is immersed in water for 60 minutes and then thoroughly dried are both found to satisfy the relationship of the following formula (I): θA'-θA≧5° (I)

[0011] Furthermore, according to the present invention, there is provided an inkjet recording method for ejecting ink from an inkjet recording head to record an image on a recording medium, characterized in that the ink is an aqueous ink containing a pigment, and the recording medium is any one of the recording media described above. Effect of the Invention

[0012] According to the present invention, it is possible to provide a recording medium that exhibits excellent water resistance that allows it to be displayed outdoors, is less susceptible to beading even when using aqueous ink, and allows high-quality images to be recorded on it. Also, according to the present invention, it is possible to provide a recording medium that has an ink-receiving layer that is excellent in ink absorbency and durability that allows it to be displayed outdoors. Furthermore, according to the present invention, it is possible to provide an inkjet recording method that allows high-quality images to be recorded on it. [Brief description of the drawings]

[0013] [Figure 1] FIG. 4 is a graph showing the change over time in the contact angle of the surface of an ink receiving layer with water. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] <Recording Media> The present invention will be described in further detail below with reference to preferred embodiments. Hereinafter, the recording medium for inkjet printing may be simply referred to as the "recording medium".

[0015] 1. First recording medium First, an embodiment of the first recording medium of the present invention will be described. In order to obtain water resistance that allows outdoor display, it is effective to use a water-insoluble resin as a binder for the ink receiving layer instead of a general water-soluble resin. By incorporating a water-insoluble resin as a binder, the contact angle of the ink receiving layer with respect to water is increased, and excellent water resistance that repels rainwater and the like can be obtained.

[0016] When a recorded matter is to be displayed outdoors, it is preferable to record the image using a water-based ink (hereinafter also simply referred to as "pigment ink") that contains a pigment with excellent water resistance as a coloring material in order to prevent the coloring material in the image from dissolving in rainwater. In order to improve the color development of an image recorded with a pigment ink, it is necessary to keep the pigment in the ink applied to the recording medium on the surface of the recording medium as much as possible. In particular, since an ink receiving layer that contains a water-insoluble resin as a binder tends to increase haze, it is particularly important to keep the pigment on the surface of the recording medium (ink receiving layer) in order to improve the color development of the image.

[0017] In order to keep the pigment on the surface of the ink-receiving layer, it is necessary to adjust the type of inorganic particles and water-insoluble resin. However, depending on the combination of inorganic particles and water-insoluble resin, the hydrophobicity of the surface of the ink-receiving layer may increase and the secondary pores that promote the ink absorption may not be substantially present in the ink-receiving layer. As a result, the ink becomes less likely to spread immediately after being applied to the ink-receiving layer, and beading is more likely to occur.

[0018] The present inventors have conducted extensive research to obtain a recording medium that suppresses the occurrence of beading while maintaining excellent water resistance. As a result, they have found the following configuration and completed the present invention. That is, an ink receiving layer (1) containing specific inorganic particles (first inorganic particles) and a water-insoluble resin (first binder) is provided under an ink receiving layer (2) disposed on the outermost surface. Then, the contact angle θ1 of the surface of the ink receiving layer (1) with water one second after contacting the surface of the ink receiving layer (1) with water is set to 90° or more. By setting the contact angle θ1 of the surface of the ink receiving layer (1) with water to 90° or more, it is possible to achieve excellent water resistance.

[0019] Furthermore, the ink receiving layer (2) disposed on the outermost surface contains second inorganic particles and a water-insoluble resin (second binder), and the thickness of the ink receiving layer (2) is set to 10 nm or more and 4,000 nm or less. The contact angle θ2 of the surface of the ink receiving layer (2) with water 1 second after the surface of the ink receiving layer (2) is brought into contact with water is set to 60° or more and 85° or less. This makes it possible to efficiently suppress beading. By disposing the ink receiving layer (2) having a contact angle θ2 with water of 60° or more and 85° or less on the outermost surface, it is possible to improve the wetting and spreading of ink on the surface of the ink receiving layer (2) while maintaining water resistance. Furthermore, the ink absorption amount per unit area is reduced by improving the wettability of the ink on the surface of the ink receiving layer (2). This makes it possible to reduce the liquid components in the ink that remain on the surface of the ink receiving layer (2), and as a result, it is possible to suppress beading. Furthermore, if the thickness of the ink receiving layer (2) is less than 10 nm, the contact angle θ2 cannot be set to 85° or less due to the influence of the ink receiving layer (1) disposed below the ink receiving layer (2), making it difficult to suppress beading. On the other hand, if the thickness of the ink receiving layer (2) is more than 4,000 nm, the proportion of the ink receiving layer (2), which has lower water resistance than the ink receiving layer (1), in the entire ink receiving layer increases, and the water resistance of the recording medium decreases. The configuration of the first recording medium of the present invention will be described in detail below.

[0020] (base material) Examples of the substrate include those made of only a base paper, those made of only a plastic film, and those made of only a cloth. Substrates having a laminated structure in which multiple layers are laminated can also be used. Specifically, those having a base paper and a resin layer, that is, resin-coated substrates, can be mentioned. Among them, from the viewpoint of outdoor display, it is preferable to use a resin-coated substrate, a plastic film, or a cloth as the substrate.

[0021] The thickness (film thickness) of the substrate is preferably 50 μm or more and 400 μm or less, and more preferably 70 μm or more and 200 μm or less. The thickness of the substrate can be measured and calculated according to the following method. First, the cross section of the recording medium cut out with a microtome is observed with a scanning electron microscope. Then, the thickness of 100 or more arbitrary points of the substrate is measured, and the average value is taken as the thickness of the substrate. The thickness of layers (films) other than the substrate is also measured and calculated in the same manner.

[0022] (1) Resin-coated substrate [Base paper] The base paper is made from wood pulp as the main raw material, and synthetic pulp such as polypropylene and synthetic fibers such as nylon and polyester are added as necessary. Examples of wood pulp include bleached hardwood kraft pulp (LBKP), bleached hardwood sulfite pulp (LBSP), bleached softwood kraft pulp (NBKP), bleached softwood sulfite pulp (NBSP), dissolving hardwood pulp (LDP), dissolving softwood pulp (NDP), unbleached hardwood kraft pulp (LUKP), and unbleached softwood kraft pulp (NUKP). These wood pulps can be used alone or in combination of two or more. Among wood pulps, it is preferable to use LBKP, NBSP, LBSP, NDP, and LDP, which have a high short fiber content. As the pulp, chemical pulp with few impurities (sulfate pulp and sulfite pulp) is preferable. Pulp that has been bleached to improve the whiteness is also preferable. The base paper may contain, as appropriate, sizing agents, white pigments, paper strength agents, fluorescent whitening agents, moisture retaining agents, dispersants, softening agents, and the like.

[0023] The thickness of the base paper is preferably 50 μm or more and 130 μm or less, and more preferably 90 μm or more and 120 μm or less. The paper density of the base paper as specified in JIS P 8118:2014 is 0.6 g / cm 3 More than 1.2g / cm 3 It is preferable that the concentration is 0.7 g / cm or less. 3 More than 1.2g / cm 3 It is even more preferable that:

[0024] [Resin layer] When the base paper is coated with a resin, the resin layer may be provided so as to cover a part of the surface of the base paper. The coverage of the resin layer (surface area of ​​the base paper coated with the resin layer / total surface area of ​​the base paper) is preferably 70% or more, more preferably 90% or more, and particularly preferably 100%, i.e., the entire surface of the base paper is coated with the resin layer.

[0025] The thickness of the resin layer is preferably 20 μm or more and 60 μm or less, and more preferably 35 μm or more and 50 μm or less. When the resin layer is provided on both sides of the base paper, it is preferable that the thickness of the resin layer on both sides each satisfy the above range.

[0026] The resin used in the resin layer is preferably a thermoplastic resin. Examples of the thermoplastic resin include acrylic resin, acrylic silicone resin, polyolefin resin, and styrene-butadiene copolymer. Among them, polyolefin resin is preferable. Polyolefin resin means a polymer using olefin as a monomer. Specific examples of polyolefin resin include homopolymers and copolymers of ethylene, propylene, isobutylene, and the like. The polyolefin resin can be used alone or in combination of two or more kinds. Among them, polyethylene is preferable. As the polyethylene, low density polyethylene (LDPE) and high density polyethylene (HDPE) are preferable.

[0027] The resin layer may contain a white pigment, a fluorescent whitening agent, ultramarine blue, etc., in order to adjust the opacity, whiteness, and hue. Of these, it is preferable to contain a white pigment, since this can improve the opacity. Examples of the white pigment include rutile or anatase titanium oxide. The content of the white pigment in the resin layer is 3 g / m 2 More than 30g / m 2It is preferable that the total content of the white pigment in the resin layers on both sides of the base paper is within the above range. The content of the white pigment in the resin layer is preferably 25% by mass or less relative to the resin content. If it exceeds 25% by mass, the dispersion stability of the white pigment may be insufficient.

[0028] The arithmetic mean roughness Ra of the resin layer as defined by JIS B 0601:2001 is preferably 0.12 μm or more and 0.18 μm or less, more preferably 0.13 μm or more and 0.15 μm or less. The mean length RSm of the roughness curve element of the resin layer as defined by JIS B 0601:2001 is preferably 0.01 mm or more and 0.20 mm or less, more preferably 0.04 mm or more and 0.15 mm or less.

[0029] (2) Plastic film In this specification, "plastic" means a material containing 50% by mass or more of polymers having a molecular weight of 10,000 or more, and "plastic film" means a plastic processed into a film. The plastic used in the plastic film is a thermoplastic plastic. Specific examples include vinyl plastics, polyester plastics, cellulose ester plastics, polyamide plastics, and heat-resistant engineering plastics.

[0030] Examples of vinyl-based plastics include polyethylene, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polystyrene, polypropylene, and fluorine-based resins. Examples of polyester-based plastics include polycarbonate and polyethylene terephthalate. Examples of cellulose ester-based plastics include cellulose diacetate, cellulose triacetate, and cellulose acetate butyrate. Examples of polyamide-based plastics include nylon 6, nylon 66, and nylon 12. Examples of heat-resistant engineering plastics include polyimide, polysulfone, polyethersulfone, polyphenylene sulfide, polyetheretherketone, and polyetherimide. These plastics may be used alone or in combination of two or more. From the viewpoints of durability and cost, it is preferable to use polyvinyl chloride, polypropylene, polycarbonate, and polyethylene terephthalate.

[0031] Synthetic paper, which has been treated with chemicals, surface coating, and internal addition to increase the opacity of plastic, can also be used as the plastic film. As an example of chemical treatment, a method can be used in which the surface of the plastic film is immersed in an organic solvent such as acetone or methyl isobutyl ketone to generate a swelling layer, and the swelling layer is dried and solidified with another organic solvent such as methanol. As an example of surface coating, a method can be used in which a layer made of a white pigment such as calcium carbonate or titanium oxide and a binder is formed on the surface of the plastic. As an example of internal addition, a method can be used in which a pigment such as calcium carbonate, titanium oxide, zinc oxide, white carbon, clay, talc, or barium sulfate is mixed into the plastic as a filler. Furthermore, a foamed plastic film can be used in which voids are formed in the plastic by adding polybutylene terephthalate fine particles, polycarbonate fine particles, polyester resin, polycarbonate resin, or the like to the plastic to increase the opacity.

[0032] The thickness of the plastic film is preferably 50 μm or more and 300 μm or less, more preferably 75 μm or more and 135 μm or less. The glass transition point of the plastic constituting the plastic film is preferably -20° C. or more and 150° C. or less, more preferably -20° C. or more and 80° C. or less. The glass transition point can be measured, for example, by differential scanning calorimetry (DSC method).

[0033] The density of plastic film (plastic density) specified in JIS K 7112:1999 is 0.6g / cm 3 More than 1.5g / cm 3 It is preferable that the concentration is 0.7 g / cm or less. 3 More than 1.4g / cm 3 The water absorption rate of the plastic film as defined in JIS K 7209:2000 is preferably 5% by mass or less, and more preferably 1% by mass or less.

[0034] By subjecting the plastic film to a surface oxidation treatment, the adhesion between the ink receiving layer and the plastic film can be improved. Examples of surface oxidation treatments include corona discharge treatment, frame treatment, plasma treatment, glow discharge treatment, and ozone treatment. These treatments can be performed alone or in combination of two or more. Of these, ozone treatment is preferred. The treatment amount is 10 to 200 (W·min) / m. 2 It is preferable to set the maximum allowable load to 50-150 (W min) / m 2 It is more preferable that:

[0035] (3) Cross In this specification, "cloth" refers to a material made by processing a large number of fibers into a thin, wide sheet. Types of fibers include natural fibers, materials with the properties of natural fibers, recycled fibers recycled from plastics, and synthetic fibers made from polymers such as petroleum. Natural fibers include cotton, silk, hemp, mohair, wool, and cashmere. Recycled fibers include acetate, cupra, rayon, and recycled polyester. Synthetic fibers include nylon, polyester, acrylic, vinylon, polyethylene, polypropylene, polyamide, and polyurethane.

[0036] (Ink Receiving Layer) An ink receiving layer (1) is provided on the substrate. Furthermore, an ink receiving layer (2) is provided on the ink receiving layer (1) to be disposed on the outermost surface of the recording medium. That is, the ink receiving layer has two or more layers including the ink receiving layer (1) and the ink receiving layer (2). The contact angle θ1 of the surface of the ink receiving layer (1) with water one second after the surface of the ink receiving layer (1) is brought into contact with water is 90° or more. There is no particular upper limit to the contact angle θ1 of the surface of the ink receiving layer (1) with water as long as the ink receiving layer (1) can absorb ink. Specifically, the contact angle θ1 of the surface of the ink receiving layer (1) with water is preferably 120° or less. Moreover, the contact angle θ2 of the surface of the ink receiving layer (2) with water one second after the surface of the ink receiving layer (2) is brought into contact with water is 60° or more and 85° or less. Hereinafter, when simply referring to the "ink-receiving layer", it means either the "ink-receiving layer (1)" or the "ink-receiving layer (2)". The ink-receiving layer may be provided on only one side of the substrate, or on both sides.

[0037] [Ink receiving layer (1)] The ink receiving layer (1) contains first inorganic particles and a first binder. The first binder is a water-insoluble resin.

[0038] The thickness of the ink receiving layer (1) is appropriately set depending on the required ink absorption capacity, etc. If the thickness of the ink receiving layer (1) is 25 μm or more, it is preferable because the ink absorbency can be maintained better. On the other hand, if the thickness of the ink receiving layer (1) is 50 μm or less, it is preferable because defects such as cracks are less likely to occur.

[0039] The contact angle θ1 can be measured before providing the ink receiving layer (2). Even after providing the ink receiving layer (2), the contact angle θ1 can be measured by scraping the ink receiving layer (2) using an ultra-precision polishing film or the like to expose the ink receiving layer (1).

[0040] [Ink receiving layer (2)] The ink receiving layer (2) contains second inorganic particles and a second binder. The second binder is a water-insoluble resin. That is, the first binder and the second binder are both water-insoluble resins. The first binder and the second binder may be the same or different.

[0041] The thickness of the ink receiving layer (2) is 10 nm or more and 4,000 nm or less. If the thickness of the ink receiving layer (2) is less than 10 nm, it becomes difficult to make the contact angle θ2 85° or less, and the effect of suppressing beading becomes insufficient. On the other hand, if the thickness of the ink receiving layer (2) exceeds 4,000 nm, the water resistance decreases. In addition, the thickness of the ink receiving layer (2) is preferably 10 nm or more and 500 nm or less.

[0042] For example, the mass ratio of the content of the second binder to the content of the second inorganic particles in the ink receiving layer (2) is set lower than the mass ratio of the content of the first binder to the content of the first inorganic particles in the ink receiving layer (1). This makes it possible to make the contact angle θ2 smaller than the contact angle θ1. Furthermore, by designing the contact angles θ1 and θ2 to satisfy the relationship of the following formula (1), it is possible to further improve the effect of improving water resistance and the effect of suppressing beading. θ1-θ2≧10° (1)

[0043] The surface roughness Ra of the ink receiving layer (2) is preferably 30 nm or more and 150 nm or less. By setting the surface roughness Ra of the ink receiving layer (2) in the above range, it is possible to suppress peeling off of an image recorded with a pigment ink due to rainwater, etc., and also to improve color development, thereby imparting superior fastness and color development to a recorded matter. The surface roughness Ra of the ink receiving layer (2) can be measured by observing the surface of the ink receiving layer (2) using a scanning probe microscope.

[0044] [Inorganic particles] Examples of the first inorganic particles and the second inorganic particles (hereinafter also simply referred to as "inorganic particles") include alumina hydrate, alumina, silica, colloidal silica, titanium dioxide, zeolite, kaolin, talc, hydrotalcite, zinc oxide, zinc hydroxide, aluminum silicate, calcium silicate, magnesium silicate, calcium carbonate, zirconium oxide, zirconium hydroxide, etc. The first inorganic particles and the second inorganic particles may be the same or different.

[0045] The first inorganic particles are preferably at least one selected from the group consisting of alumina hydrate, fumed alumina, and fumed silica. By using these inorganic particles as the first inorganic particles, the pigment in the ink is easily retained on the surface of the ink receiving layer, and as a result, the color development of the image can be improved.

[0046] Moreover, the second inorganic particles are preferably colloidal silica. By using colloidal silica as the second inorganic particles, the glossiness of the recording medium can be improved. The average particle size of the water-insoluble resin used as the second binder is preferably 200 nm or less in order to improve the glossiness of the recording medium. Although colloidal silica does not easily form pores that promote ink absorption, since the thickness of the ink receiving layer (2) is 4,000 nm or less, even if colloidal silica is used as the second inorganic particles, the ink absorption of the ink receiving layer (2) can be prevented from decreasing.

[0047] (1) Alumina hydrate The alumina hydrate is preferably represented by the following general formula (X). AlO 3-n (OH) 2n mH2O (X)

[0048] In the general formula (X), n represents 0, 1, 2, or 3, and m represents a number from 0 to 10, preferably 0 to 5. However, m and n cannot be 0 at the same time. mH2O often means desorbable water that is not involved in the formation of a crystal lattice. Therefore, m is an integer or a number other than an integer. In addition, m may become 0 by heating.

[0049] Alumina hydrate can be produced by known methods, such as a method of hydrolyzing aluminum alkoxide, a method of hydrolyzing sodium aluminate, and a method of neutralizing an aqueous solution of sodium aluminate by adding an aqueous solution of aluminum sulfate or aluminum chloride.

[0050] The crystal structure of alumina hydrate can be amorphous, gibbsite, or boehmite, depending on the temperature of the heat treatment. Alumina hydrate having any crystal structure can be used. Among them, alumina hydrate having a boehmite structure and amorphous alumina hydrate are preferred. The crystal structure of alumina hydrate can be analyzed by X-ray diffraction.

[0051] It is preferable that the alumina hydrate particles (alumina particles) are mixed as an aqueous dispersion into the coating liquid for the ink receiving layer. It is also preferable to use an acid as a dispersant for the alumina particles. Examples of the acid that can be used include sulfonic acid, lactic acid, glycolic acid, and acetic acid.

[0052] The average primary particle size of the alumina particles is preferably 20 nm or more and 100 nm or less, and more preferably 20 nm or more and 80 nm or less. The average primary particle size of the inorganic particles can be measured by observation with, for example, a transmission electron microscope (TEM) or a scanning electron microscope (SEM).

[0053] The average secondary particle size of the alumina particles is preferably 155 nm or more and 560 nm or less, more preferably 160 nm or more and 560 nm or less. In addition, it is particularly preferably 170 nm or more and 540 nm or less, and most preferably 190 nm or more and 250 nm or less. The average secondary particle size of the inorganic particles means the volume average particle size (hereinafter, also simply referred to as "average particle size") measured and calculated by a light scattering method. As an apparatus for measuring the average secondary particle size of the inorganic particles by a light scattering method, for example, a dynamic scattering method measuring apparatus (product name "ELS-Z", manufactured by Otsuka Electronics) can be mentioned.

[0054] By using alumina particles whose average primary particle size and average secondary particle size fall within the above ranges, it is possible to easily obtain a recording medium (ink receiving layer (2)) whose surface roughness Ra is 30 nm or more and 150 nm or less.

[0055] (2) Gas-phase alumina Examples of fumed alumina include γ-alumina, α-alumina, δ-alumina, θ-alumina, and χ-alumina. Among them, it is preferable to use γ-alumina from the viewpoint of the optical density of the image and ink absorption. Examples of commercially available fumed alumina include AEROXIDE, Alu C, Alu130, and Alu65 (all manufactured by EVONIK) under the following trade names.

[0056] The specific surface area of ​​vapor phase alumina determined by the BET method is 50m 2 / g or more 150m 2 / g or less, and 2 / g or more 120m 2The average primary particle size of the fumed alumina is preferably 5 nm or more and 30 nm or less, and more preferably 11 nm or more and 15 nm or less.

[0057] The fumed alumina is preferably mixed as an aqueous dispersion into the coating liquid for the ink receiving layer. An acid is preferably used as a dispersant for the fumed alumina. Examples of the acid that can be used include sulfonic acid, lactic acid, glycolic acid, and acetic acid. The average secondary particle size of the fumed alumina in the dispersed state is preferably 50 nm or more and 300 nm or less. The average secondary particle size of the fumed alumina in the dispersed state can be measured by dynamic light scattering.

[0058] (3) Gel-based silica Silica is roughly classified into wet method and dry method (gas phase method) according to the manufacturing method. As a wet method, a method is known in which activated silica generated by acid decomposition of silicate is moderately polymerized, and then coagulated and precipitated to obtain hydrated silica. Gel method silica can be manufactured, for example, by the following method. First, silicate and inorganic acid are reacted to produce silica hydrosol so that the SiO2 concentration is 10 to 20 mass%, and the silica hydrosol is gelled to obtain silica hydrogel. As silicate, sodium silicate, potassium silicate, ammonium silicate, etc. can be used. Sodium silicate is often used industrially. As inorganic acids, sulfuric acid, nitric acid, hydrochloric acid, etc. can be mentioned. Sulfuric acid is generally used. Next, the obtained silica hydrogel is washed with water to remove the inorganic acid salt contained in the silica hydrogel.

[0059] The average pore size and oil absorption can be adjusted by controlling the conditions for hydrothermal treatment of silica hydrogel from which inorganic acid salts have been removed. For example, when silica hydrogel is hydrothermally treated with water having a pH of 2 to 10 and a temperature of 20 to 100°C, the average pore size and oil absorption increase. That is, the average pore size and oil absorption of silica gel can be adjusted by appropriately setting the pH and temperature of water used in hydrothermal treatment and the treatment time. Considering the balance of the physical properties of silica gel, it is preferable to perform hydrothermal treatment with water having a pH of 2 to 8 and a temperature of 40 to 90°C. The silica hydrogel is pulverized with a ball mill or the like to obtain silica particles having an average secondary particle size of several μm, and then dried at 100 to 1,000°C for 1 to 100 seconds to obtain gel-method silica.

[0060] (4) Fumed silica As the dry method (vapor phase method), a method of high-temperature vapor phase hydrolysis of silicon halide (flame hydrolysis method) and a method of reducing and vaporizing silica sand and coke by heating with an arc in an electric furnace and oxidizing it with air (arc method) to obtain anhydrous silica are known. Among them, it is preferable to use silica obtained by the dry method (vapor phase method) (vapor phase silica). Vapor phase silica has a particularly large specific surface area, and is therefore preferable because it can increase the ink absorption. In addition, vapor phase silica has a low refractive index, and therefore can impart transparency to the ink receiving layer and improve the color development of the image. Commercially available vapor phase silica products include Aerosil (manufactured by Nippon Aerosil); Reolosil QS type (manufactured by Tokuyama), etc., under the following trade names.

[0061] The specific surface area of ​​vapor-phase silica determined by the BET method is 50 m 2 / g or more 400m 2 / g or less, and 2 / g or more 350m 2 It is more preferable that the molecular weight is not more than 1 / g.

[0062] The gas phase silica is preferably mixed as an aqueous dispersion into the coating liquid for the ink receiving layer. In addition, it is preferable to use a cationic resin or a polyvalent metal salt as a dispersant for the gas phase silica. Examples of the cationic resin include polyethyleneimine resin, polyamine resin, polyamide resin, polyamide epichlorohydrin resin, polyamine epichlorohydrin resin, polyamide polyamine epichlorohydrin resin, polydiallylamine resin, and dicyandiamide condensate. Examples of the polyvalent metal salt include aluminum compounds such as polyaluminum chloride, polyaluminum acetate, and polyaluminum lactate.

[0063] The average secondary particle size of the fumed silica in a dispersed state is preferably 50 nm or more and 300 nm or less. The average secondary particle size of the fumed silica in a dispersed state can be measured by a dynamic light scattering method.

[0064] (5) Colloidal silica As the colloidal silica, it is preferable to use spherical colloidal silica. By using spherical colloidal silica, the gloss of the recording medium can be further increased, and the transparency is also improved, so that the color development of the recorded image can be further improved. "Spherical" means that the ratio of the average minor axis b to the average major axis a (b / a value) of colloidal silica particles (50 or more and 100 or less) observed by a scanning electron microscope is 0.80 or more and 1.00 or less. The b / a value of colloidal silica is preferably 0.90 or more and 1.00 or less, and more preferably 0.95 or more and 1.00 or less.

[0065] The colloidal silica is preferably cationized, and spherical cationic colloidal silica is more preferable. Commercially available spherical cationic colloidal silica products include the following trade names: PL-3, PL-7 (all manufactured by Fuso Chemical Industry); Snowtex AK, Snowtex AK-L, MP-2040 (all manufactured by Nissan Chemical Industries); Cartacoat K303C (manufactured by Clariant); etc. From the viewpoint of further improving ink absorption and color development of images, the average primary particle size of the colloidal silica is preferably 10 nm or more and 100 nm or less.

[0066] [Binder] The first binder contained in the ink receiving layer (1) and the second binder contained in the ink receiving layer (2) are both water-insoluble resins. In this specification, the term "binder" refers to a material that can bind inorganic particles and form a coating. In addition, in this specification, the term "water-insoluble resin" refers to a resin of which 95% by mass or more remains when immersed in 80°C hot water for 2 hours.

[0067] From the viewpoint of water resistance, the water-insoluble resin is preferably at least one selected from the group consisting of acrylic resins, polycarbonate-modified urethane resins, and polyether-modified urethane resins.

[0068] [Water-insoluble resin] (1) Acrylic resin In this specification, the term "acrylic resin" refers to a polymer of a (meth)acrylic acid ester. As long as a (meth)acrylic acid ester is used as a monomer, the polymer may be a homopolymer or a copolymer with other monomers.

[0069] Examples of acrylic acid esters include methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, 2-dimethylaminoethyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, isobutyl acrylate, octyl acrylate, lauryl acrylate, stearyl acrylate, etc. Examples of methacrylic acid esters include methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, 2-dimethylaminoethyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, isobutyl methacrylate, octyl methacrylate, lauryl methacrylate, stearyl methacrylate, etc.

[0070] Other monomers that can be copolymerized with (meth)acrylic acid esters include vinyl monomers, such as styrene, vinyl toluene, vinyl benzoic acid, α-methylstyrene, p-hydroxymethylstyrene, and styrene sulfonic acid, and their derivatives; and vinyl ethers such as methyl vinyl ether, butyl vinyl ether, methoxyethyl vinyl ether, N-vinylpyrrolidone, 2-vinyloxazone, and vinyl sulfonic acid, and their derivatives.

[0071] As the acrylic resin, polyacrylic acid ester, polymethacrylic acid ester, and copolymer of acrylic acid ester and methacrylic acid ester are preferable. Among them, copolymer of methacrylic acid ester and acrylic acid ester is preferable because the glass transition temperature of the obtained acrylic resin can be controlled by designing the copolymerization ratio of methacrylic acid ester and acrylic acid ester.

[0072] (2) Urethane resin In this specification, the term "urethane resin" refers to a resin having a urethane bond in its structure. As the urethane resin, at least one of a polycarbonate-modified urethane resin and a polyether-modified urethane resin is used. Hereinafter, the polycarbonate-modified urethane resin and the polyether-modified urethane resin are collectively referred to simply as "urethane resin".

[0073] The urethane resin can be obtained by reacting a polyisocyanate, a polyol, and a chain extender. Examples of the polyisocyanate include aromatic isocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, polymeric diphenylmethane diisocyanate, tolidine diisocyanate, naphthalene diisocyanate, xylylene diisocyanate, and tetramethylxylylene diisocyanate; and aliphatic and alicyclic isocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and isophorone diisocyanate.

[0074] Examples of polyols include polyether polyols such as polypropylene glycol, polyethylene glycol, and polytetramethylene glycol; and polycarbonate polyols such as polyhexamethylene carbonate. Examples of chain extenders include compounds having active hydrogen atoms, such as low molecular weight glycols such as ethylene glycol, low molecular weight diamines, and low molecular weight amino alcohols. These components can be used alone or in combination of two or more.

[0075] The glass transition point (Tg) of the water-insoluble resin is preferably 20° C. or lower. By using a water-insoluble resin having a glass transition point of 20° C. or lower, the binding strength between the binder and the inorganic particles is further improved, and the water resistance of the ink receiving layer can be further improved. The glass transition point of the water-insoluble resin can be measured, for example, by differential scanning calorimetry (DSC method).

[0076] From the viewpoint of ink absorbency, the content of the first binder in the ink receiving layer (1) is preferably 70% by mass or less, and more preferably 50% by mass or less, based on the content of the first inorganic pigment. From the viewpoint of the binding property of the ink receiving layer, the content of the first binder in the ink receiving layer (1) is preferably 25% by mass or more, and more preferably 30% by mass or more, based on the content of the first inorganic pigment. Furthermore, from the viewpoint of water resistance, it is preferable that the ink receiving layer (1) contains 14% by mass or less of the first water-soluble resin, or does not contain the first water-soluble resin, based on the content of the first binder in the ink receiving layer (1).

[0077] From the viewpoint of ink absorbency and beading suppression, the content of the second binder in the ink receiving layer (2) is preferably 50% by mass or less, and more preferably 40% by mass or less, based on the content of the second inorganic pigment. From the viewpoint of the binding property of the ink receiving layer, the content of the second binder in the ink receiving layer (2) is preferably 15% by mass or more, and more preferably 20% by mass or more, based on the content of the second inorganic pigment. Furthermore, from the viewpoint of water resistance, it is preferable that the ink receiving layer (2) contains 14% by mass or less of the second water-soluble resin, or does not contain the second water-soluble resin, based on the content of the second binder in the ink receiving layer (2).

[0078] [Water-soluble resin] The ink receiving layer (1) and the ink receiving layer (2) may contain a first water-soluble resin and a second water-soluble resin as binders, respectively. Hereinafter, the "first water-soluble resin" and the "second water-soluble resin" are collectively referred to as "water-soluble resins".

[0079] Examples of the water-soluble resin include polyvinyl alcohol, polyvinylpyrrolidone, water-soluble cellulose, etc. From the viewpoint of water resistance, it is preferable that the ink receiving layer (i) does not contain a water-soluble resin; or (ii) contains a water-soluble resin in an amount of 14 mass% or less relative to the water-insoluble resin. The ratio of the content of the water-soluble resin to the content of the water-insoluble resin in the ink receiving layer can be measured and calculated by the method shown below, in addition to being calculated from the raw materials used to form the ink receiving layer.

[0080] First, 10 g of the ink receiving layer scraped off from the recording medium is poured into 1,000 g or more of warm water (80°C or higher), stirred, and then filtered. The filtrate is dried and the mass of the solid content obtained is measured (defined as X(g)). The value calculated as "10(g) - X(g)" is defined as the content of the water-soluble resin in 10 g of the ink receiving layer. Next, the solid content of X(g) is heated at 600°C for 2 hours, and the mass of the resulting residue is measured (defined as Y(g)). The value calculated as "X(g) - Y(g)" is defined as the content of the water-insoluble resin in 10 g of the ink receiving layer.

[0081] The ratio of the water-soluble resin content to the water-insoluble resin content can be calculated by the formula: [10(g)-X(g)] / [X(g)-Y(g)]. The ratio of the water-insoluble resin content to the inorganic particle content can be calculated by the formula: [(X(g)-Y(g)] / [Y(g)].

[0082] [Other additives] The ink receiving layer may contain additives other than the above-mentioned various components, such as a crosslinking agent, a pH adjuster, a thickener, a flow improver, an antifoaming agent, a foam suppressor, a surfactant, a release agent, a penetrating agent, a coloring pigment, a coloring dye, a fluorescent brightener, an ultraviolet absorbing agent, an antioxidant, a preservative, an antifungal agent, a water resistant agent, an ink fixing agent, a hardener, and a high fastness material.

[0083] Examples of the crosslinking agent include aldehyde compounds, melamine compounds, isocyanate compounds, zirconium compounds, titanium compounds, amide compounds, aluminum compounds, boric acid, borates, carbodiimide compounds, oxazoline compounds, etc. Examples of the ink fixing agent include cationic resins other than the above-mentioned acrylic resins and urethane resins, and polyvalent metal salts.

[0084] Examples of the cationic resin include polyethyleneimine resins, polyamine resins, polyamide resins, polyamide epichlorohydrin resins, polyamine epichlorohydrin resins, polyamide polyamine epichlorohydrin resins, polydiallylamine resins, and dicyandiamide condensates. Examples of the polyvalent metal salt include calcium compounds, magnesium compounds, zirconium compounds, titanium compounds, and aluminum compounds. Among these, calcium compounds are preferred, and calcium nitrate tetrahydrate is more preferred.

[0085] In order to improve ink absorbency and suppress beading, it is preferable that the ink receiving layer contains a surfactant. Examples of the surfactant include acetylene-based surfactants, fluorine-based surfactants, silicone-based surfactants, polyether-modified silicone-based surfactants, polysiloxane-based surfactants, and ether-modified polysiloxane-based surfactants. Among these, acetylene-based surfactants are preferable.

[0086] (Method of manufacturing recording medium) The method for producing the above-mentioned recording medium is not particularly limited. For example, it is preferable to produce the recording medium by a production method including a step of preparing a coating liquid for the ink receiving layer (1) and a coating liquid for the ink receiving layer (2) (coating liquid preparation step) and a step of applying the prepared coating liquids to a substrate (coating step).

[0087] In the coating liquid preparation step, a coating liquid for the ink receiving layer (1) and a coating liquid for the ink receiving layer (2) are prepared. These coating liquids can be prepared by mixing the above-mentioned components according to a standard method.

[0088] In the coating step, each of the prepared coating liquids is applied to a substrate to form a coating layer. The coating liquid for the ink-receiving layer (1) and the coating liquid for the ink-receiving layer (2) are applied sequentially or simultaneously. Of these, sequential application of the coating liquid for the ink-receiving layer (1) and the coating liquid for the ink-receiving layer (2) is preferred because mixing of the coating liquids can be suppressed.

[0089] To apply the coating liquid to the substrate, a gate roll coater, a size press, a bar coater, a blade coater, an air knife coater, a roll coater, a brush coater, a curtain coater, a gravure coater, a spray device, etc. may be used. The coating liquid may be appropriately heated before application.

[0090] It is preferable to dry the coating layer formed by applying each coating liquid to a substrate. To dry the coating layer, a hot air dryer such as a linear tunnel dryer, an arch dryer, an air loop dryer, or a sine curve air float dryer can be used. In addition, a dryer using infrared rays, a heating dryer, or a microwave can also be used. The heating temperature during drying can be, for example, 80 to 130°C.

[0091] Before applying the coating liquid to the substrate, a surface treatment liquid containing a surface treatment agent may be applied to the surface of the substrate (the surface to which the coating liquid is applied). By applying the surface treatment liquid to the surface of the substrate in advance, the wettability of the coating liquid to the substrate is increased, and the adhesion between the ink receiving layer to be formed and the substrate can be improved. Examples of the surface treatment agent include thermoplastic resins such as acrylic resins, polyurethane resins, polyester resins, polyethylene resins, polyvinyl chloride resins, polypropylene resins, polyamide resins, and styrene-butadiene copolymers; silane coupling agents; and the like. The surface treatment liquid may contain inorganic particles such as titanium oxide, calcium carbide, silica, and alumina, as necessary.

[0092] 2. Second Recording Medium Next, a second embodiment of the recording medium of the present invention will be described. The present inventors conducted extensive research to provide a recording medium having an ink-receiving layer with excellent ink absorbency and durability for outdoor display. As a result, they found that the above object can be achieved by adopting the following configuration, and completed the present invention. That is, an ink-receiving layer (1) containing specific inorganic particles (first inorganic particles) and a water-insoluble resin (first binder) is provided under the ink-receiving layer (2) arranged on the outermost surface. This makes it possible to achieve excellent durability for outdoor display.

[0093] Furthermore, the ink receiving layer (2) disposed on the outermost surface contains second inorganic particles and a water-insoluble resin (second binder), and the thickness of the ink receiving layer (2) is set to 10 nm or more and 4,000 nm or less. The contact angle θA of the surface of the ink receiving layer (2) with water 60 seconds after the surface of the ink receiving layer (2) is brought into contact with water is 40° or more and 80° or less. The contact angle θA and the contact angle θA of the surface of the ink receiving layer (2) with water 60 seconds after the recording medium is immersed in water for 60 minutes and then thoroughly dried are brought into contact with water, and the relationship of the following formula (I) is satisfied. θA'-θA≧5° (I)

[0094] The present inventors speculate that the reason why the above-mentioned configuration improves ink absorbency and durability for outdoor display is as follows. By making the contact angle θA of the surface of the ink receiving layer with water 40° or more 60 seconds after the surface of the ink receiving layer (2) is brought into contact with water, the water repellency effect is significantly improved, and an ink receiving layer exhibiting excellent durability can be obtained. In addition, by making the contact angle of water with the surface of the ink receiving layer (2) 60 seconds after the surface of the ink receiving layer (2) is brought into contact with water 80° or less, beading can be suppressed. Furthermore, by making the contact angle θA' and the contact angle θA satisfy the relationship of the above formula (I), the contact angle of the recorded matter increases after the recorded matter on which an image is recorded is displayed outdoors and exposed to rainwater. This significantly improves the water repellency of the surface of the ink receiving layer (2), and the durability of the ink receiving layer can be increased to the point where it can be displayed outdoors.

[0095] The configuration and manufacturing method of the second recording medium can be the same as those of the first recording medium. In particular, the ink receiving layer (2) of the second recording medium preferably contains a surfactant having an HLB value of more than 10, and more preferably contains a surfactant having an HLB value of 13 or more. By containing a surfactant having an HLB value of more than 10 in the ink receiving layer (2), the contact angle θA of the surface of the ink receiving layer (2) with water can be adjusted to 40° or more and 80° or less, and beading can be suppressed. Furthermore, when a recorded matter on which an image is recorded is displayed outdoors and exposed to rainwater, at least a part of the surfactant having an HLB value of more than 10 dissolves in the rainwater and flows out of the ink receiving layer (2). As a result, the second binder, which is a water-insoluble resin remaining in the ink receiving layer (2), makes the contact angle of the surface of the ink receiving layer (2) with water (contact angle θA') 5° or more higher than the contact angle (contact angle θA) before exposure to rainwater. Therefore, an ink receiving layer having excellent durability and suitable for outdoor display can be obtained. The HLB value of a surfactant is a value calculated by the following formula (Griffin's formula). HLB value = (molecular weight of hydrophilic group / molecular weight of entire surfactant) x 20

[0096] (Contact angle of the surface of the ink receiving layer (2) with water) The contact angle of the surface of the ink receiving layer (2) with water (contact angle θA, contact angle θA') can be measured using a dynamic contact angle tester (for example, product name "1100DAT" (manufactured by FIBRO)). Specifically, 4 μL of pure water is dropped onto the surface of the ink receiving layer (2), and the state after the dropping is videotaped. Then, after a required time has elapsed, the contact angle of the droplet (water) on the surface of the ink receiving layer (2) is measured from the video image.

[0097] FIG. 1 is a diagram showing the change over time in the contact angle between the surface of the ink receiving layer and water. Specifically, the diagram shows the change over time in the contact angle between the surface of the ink receiving layer (2) and water for 60 seconds after water is brought into contact with the surface of the ink receiving layer (2) for a recording medium (1) and a recording medium (2) obtained by thoroughly drying the recording medium (1) after immersing it in water for 60 minutes. As shown in FIG. 1, the contact angle θA of the ink receiving layer (2) of the recording medium (1) is 40° or more and 80° or less, and therefore has excellent ink absorbency. In addition, the contact angle θA' of the ink receiving layer (2) of the recording medium (2) is 5° or more larger than the contact angle θA.

[0098] The contact angle θA of the surface of the ink receiving layer (2) with water 60 seconds after contacting the surface of the ink receiving layer (2) with water is 40° or more and 80° or less. It can be determined that the contact angle θA and the contact angle θA' of the ink receiving layer (2) 60 seconds after contacting with water are both almost steady. The contact angles θA and θA' preferably become steady before 40 seconds have elapsed since contacting with water, more preferably before 20 seconds have elapsed, and particularly preferably before 10 seconds have elapsed.

[0099] <Inkjet recording method> Next, the inkjet recording method of the present invention will be described. The inkjet recording method of the present invention is a method in which ink is ejected from an inkjet recording head and applied to the above-mentioned recording medium, thereby recording an image on the recording medium. Methods for ejecting ink include a method for ejecting ink by applying mechanical energy to the ink, and a method for ejecting ink by applying thermal energy to the ink. As the ink, a water-based ink (water-based pigment ink) containing a pigment as a coloring material is used.

[0100] (Water-based pigment ink) Aqueous pigment inks usually contain water and pigments. Aqueous pigment inks can further contain water-soluble organic solvents and other components as necessary. Examples of other components include viscosity adjusters, pH adjusters, preservatives, surfactants, and antioxidants.

[0101] The water used is preferably deionized water or ion-exchanged water. The water content (mass %) in the ink is preferably 50.0% to 95.0% by mass based on the total mass of the ink. The water-soluble organic solvent content (mass %) in the ink is preferably 3.0% to 50.0% by mass based on the total mass of the ink.

[0102] As the pigment, a known pigment can be used. The average particle size of the pigment is preferably 50 nm or more and 180 nm or less. A pigment having an average particle size within the above range is more likely to remain on the surface of the recording medium, so that peeling off of the pigment from the recording medium can be further suppressed. EXAMPLES

[0103] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples without departing from the gist of the present invention. "Parts" and "%" used to describe the amounts of components are based on mass unless otherwise specified.

[0104] 1. Example 1 <Preparing the substrate> As a substrate, polypropylene synthetic paper (product name "New Yupo GCR110", manufactured by Yupo Corporation) was prepared.

[0105] <Preparation of inorganic particle dispersion> (Inorganic particle dispersion 1A~1E) An inorganic particle dispersion liquid was prepared containing the types and amounts of inorganic particles and dispersant shown in Table 1. Specifically, the inorganic particles were added while stirring a mixture of pure water and dispersant with a mixer. After the inorganic particles were added, the mixture was further stirred with the mixer for 30 minutes to disperse the inorganic particles, and an inorganic particle dispersion liquid was obtained. The average particle size of the inorganic particles in the obtained inorganic particle dispersion liquid was measured by the following procedure.

[0106] Measurement samples were prepared by diluting each of the inorganic particle dispersions 1A to 1E with pure water to a solid content of 1%. The average particle size (average secondary particle size) of the inorganic particles in the inorganic particle dispersions 1A to 1D was measured using a dynamic scattering method measuring device (product name "ELS-Z", manufactured by Otsuka Electronics). In addition, since the particle size of the wet silica used in the inorganic particle dispersion 1E was large, the average particle size (average primary particle size) of the inorganic particles was measured using a laser diffraction type particle size distribution measuring device (product name "SALD-2300", manufactured by Shimadzu Corporation). Details of each component in Table 1 are shown below. ·Alumina hydrate 1: Product name “HP30”, manufactured by Sasol ·Alumina hydrate 2: Product name “HP15”, manufactured by Sasol Gas-phase alumina: Product name "AluminaC", manufactured by EVONIK Gas-phase silica: Product name "Aerosil 200", manufactured by Nippon Aerosil Wet silica: Product name "Sylisia660", manufactured by Fuji Silysia Chemical

[0107] TIFF0007631114000001.tif66170

[0108] <Preparation of Coating Solution for Ink Receiving Layer (1)> (Coating Liquid 1-1 to 1-11) The types and amounts of each component shown in Table 2 were mixed, and 2.5 parts of a benzotriazole type ultraviolet absorber was added to 100 parts of inorganic particles. Pure water was then added to adjust the solid content, to obtain Coating Liquids 1-1 to 1-11. Details of each component in Table 2 are shown below. Acrylic resin: Mowinyl 6950, manufactured by Nippon Synthetic Polycarbonate modified urethane resin: Product name "WLS210", manufactured by DIC Polyether modified urethane resin: Product name "WLS201", manufactured by DIC Polyester modified urethane resin: Product name "NS310X", made by Takamatsu Oil Polyvinyl alcohol: Product name "PVA235", manufactured by Kuraray

[0109] TIFF0007631114000002.tif132170

[0110] <Preparation of Coating Solution for Ink Receiving Layer (2)> (Coating Liquid 2-1 to 2-8) The types and amounts of each component shown in Table 3 were mixed, and then pure water was added to adjust the solid content, to obtain Coating Liquids 2-1 to 2-8. Details of each component in Table 3 are shown below. Cationic colloidal silica 1: Product name "Snowtex AK", manufactured by Nissan Chemical Cationic colloidal silica 2: Product name "Snowtex AKYL", manufactured by Nissan Chemical Industries, Ltd. Acrylic resin: Product name "Mowinyl 6940", manufactured by Nippon Synthetic Chemical Industries, Ltd. Acrylic urethane core-shell emulsion: Product name "Acrit WEM041U", manufactured by Taisei Fine Chemical Polyvinyl alcohol: Product name "PVA235", manufactured by Kuraray

[0111] TIFF0007631114000003.tif149170

[0112] <Manufacturing of recording media> The coating liquid for the ink receiving layer (1) of the type shown in Table 4 was applied onto the substrate using a bar coater so that the thickness after drying would be the thickness shown in Table 4, and the ink receiving layer (1) was formed by drying with hot air at 80°C. The contact angle θ1 between the surface of the formed ink receiving layer (1) and water was measured using a dynamic contact angle tester (product name "1100DAT", manufactured by FIBRO).

[0113] On the ink receiving layer (1), the coating liquid for the ink receiving layer (2) of the type shown in Table 4 was applied to the substrate using a bar coater so that the thickness after drying would be the thickness shown in Table 4. The ink receiving layer (2) was formed by drying with hot air at 80°C, and a recording medium was obtained. A dynamic contact angle tester (product name "1100DAT", manufactured by FIBRO) was used to measure the contact angle θ2 with water on the surface of the formed ink receiving layer (2). In addition, the cross section of the recording medium cut out with a microtome was observed with a scanning electron microscope (product name "SU-70", manufactured by Hitachi, Ltd.). Then, the thickness was measured at 100 or more arbitrary positions, and the average value was calculated to be the thickness of the ink receiving layer (1) and the ink receiving layer (2).

[0114] <Evaluation> In the evaluation criteria for each item shown below, "A" and "B" were considered to be favorable levels, and "C" was considered to be an unacceptable level. The evaluation results are shown in Table 4.

[0115] (water resistance) After running running water at 80°C on the surface of the recording medium (ink receiving layer) for 24 hours, it was dried overnight. Black paper (product name "New Color R", manufactured by Lintec) was applied to the surface of the ink receiving layer at a rate of 75 g / cm 2The test was carried out by pressing the black paper with a load of 0.01 kg and reciprocating 20 times using a Gakushin type rubbing fastness tester. The Gakushin type rubbing fastness tester used was a Gakushin type rubbing fastness tester (manufactured by Tester Sangyo) with the product name "AB-301 COLOR FASTNESS RUBBING TESTER". The rate of change in optical density of the surface of the black paper (the surface pressed against the surface of the ink receiving layer) before and after this test was measured using an optical reflection densitometer (product name "500 Spectrodensitometer", manufactured by X-Rite), and the water resistance of the recording medium was evaluated according to the evaluation criteria shown below. The higher the rate of change in optical density, the more of the scraped ink receiving layer is attached to the black paper, which means that the water resistance of the recording medium is low. A: The change in optical density was less than 20%. B: The rate of change in optical density was 20% or more and less than 30%. C: The rate of change in optical density was 30% or more.

[0116] (Beading) Using an inkjet recording device (product name "imagePROGRAF Pro4000", manufactured by Canon) equipped with water-based pigment ink, a patch of (R, G, B) = (0, 255, 0) was recorded on a recording medium in standard mode on waterproof poster synthetic paper. The patch recording conditions were a temperature of 23°C and a humidity of 50%. The recorded patch was visually observed, and beading was evaluated according to the following evaluation criteria. A: No beading was observed. B: Beading was observed, but it was not noticeable. C: Beading was observed and was at a disturbing level.

[0117] TIFF0007631114000004.tif140170

[0118] 2. Example 2 <Preparing the substrate> As a substrate, polypropylene synthetic paper (product name "New Yupo GCR110", manufactured by Yupo Corporation) was prepared.

[0119] <Preparation of Coating Solution for Ink Receiving Layer> The type of inorganic particles shown in Tables 5-1 and 5-2 were added to the mixture of pure water and dispersant while stirring it with a mixer. After the inorganic particles were added, the mixture was further stirred with the mixer for 30 minutes to disperse them, and an inorganic particle dispersion with a solid content concentration of 37% was obtained. Glycolic acid was used as the dispersant. The amount of the dispersant was 1% relative to the inorganic particles. The obtained inorganic particle dispersion was mixed with each component of the type and amount shown in Tables 5-1 and 5-2. Furthermore, pure water was added to adjust the solid content, and a coating liquid for the ink receiving layer (2) and a coating liquid for the ink receiving layer (1) were obtained. Details of each component in Tables 5-1 and 5-2 are shown below. Alumina: Product name "HP30", manufactured by Sasol Acrylic resin 1: Product name "Movinyl 6950", manufactured by Nippon Synthetic Chemical Industry Acrylic resin 2: Mowinyl 6940, manufactured by Nippon Synthetic Chemical Industry Polycarbonate modified urethane resin: Product name "Hydran WLS210", manufactured by DIC Polyether modified urethane resin: Product name "Hydran WLS201", manufactured by DIC -UV absorber: Hostavin 3315, manufactured by Clariant Polyvinyl alcohol (product name: PVA235, Kuraray Co., Ltd.) Colloidal silica: Product name "ST-AK", manufactured by Nissan Chemical Industries Acetylene glycol 1: Trade name "Olfine E1004", manufactured by Nissin Chemical Industry Co., Ltd., HLB value = 9 Acetylene glycol 2: Trade name "Surfynol 420", manufactured by Nissin Chemical Industry Co., Ltd., HLB value = 4 Acetylene glycol 3: Trade name "Surfynol 465", manufactured by Nissin Chemical Industry Co., Ltd., HLB value = 13 Acetylene glycol 4: Trade name "Surfynol 485", manufactured by Nissin Chemical Industry Co., Ltd., HLB value = 17

[0120] In addition, since the surfactants used (acetylene glycols 1 to 4) were all surfactants with a dry solid content of 100% (i.e., active ingredient content of 100%), the calculation was made as "mass of surfactant = mass of dry solid content."

[0121] <Manufacturing of recording media> The coating liquid for the ink receiving layer (1) was applied to the substrate using a bar coater so that the thickness after drying would be as shown in Table 5-1, and the coating liquid was dried with hot air at 80°C to form the ink receiving layer (1). The coating liquid for the ink receiving layer (2) was applied to the formed ink receiving layer (1) using a bar coater so that the thickness after drying would be as shown in Table 5-2. The ink receiving layer (2) was formed by drying with hot air at 80°C, and a recording medium was obtained. The cross section of the recording medium cut out with a microtome was observed with a scanning electron microscope (product name "SU-70", manufactured by Hitachi, Ltd.). Then, the thickness was measured at 100 or more arbitrary positions, and the average value was calculated to be the thickness of the ink receiving layer (1) and the ink receiving layer (2).

[0122] TIFF0007631114000005.tif181170

[0123] TIFF0007631114000006.tif143170

[0124] <Evaluation> In the evaluation criteria for each item shown below, "A", "B" and "B-" were considered to be favorable levels, and "C" was considered to be an unacceptable level. The evaluation results are shown in Table 6.

[0125] (Contact angle measurement) Using a dynamic contact angle tester (product name "1100DAT", manufactured by FIBRO), the contact angle θA of the surface of the ink receiving layer (2) with water was measured 60 seconds after the surface of the ink receiving layer (2) was brought into contact with water. Furthermore, the recording medium was immersed in water for 60 minutes and then thoroughly dried, and the contact angle θA' of the surface of the ink receiving layer (2) with water was measured 60 seconds after the surface of the ink receiving layer (2) was brought into contact with water. The measured contact angles θA and θA' are shown in Table 6. Furthermore, the calculated value of θA'-θA is shown in Table 6.

[0126] (durability) A durability test was conducted by exposing the recording medium for 600 hours using an outdoor weather resistance accelerated test method in accordance with ISO18930. The film strength of the ink receiving layer after the durability test was then measured to evaluate the durability of the ink receiving layer. Specifically, black paper (product name "New Color R", manufactured by Lintec) was applied at 75 g / cm2 to the surface of the ink receiving layer of the recording medium after the durability test. 2 The paper was pressed against the paper with a load of 0.01 mm and reciprocated 20 times using a Gakushin-type rubbing fastness tester. The Gakushin-type rubbing fastness tester used was a "AB-301 COLOR FASTNESS RUBBING TESTER" (manufactured by Tester Sangyo). An optical reflection densitometer (product name "500 Spectrodensitometer", manufactured by X-Rite) was then used to measure the optical density (OD1) of the part of the black paper that was not in contact with the surface of the ink receiving layer, and the optical density (OD2) of the part of the black paper that was in contact with the surface of the ink receiving layer. The film strength of the ink receiving layer was then calculated using the following formula. Membrane strength (%)=(OD1 / OD2)×100

[0127] The durability of the ink receiving layer was evaluated based on the calculated film strength according to the following evaluation criteria: The durability of the ink receiving layer of each recording medium before the durability test was rated "A". A: The film strength was 80% or more. B: The film strength was 65% or more and less than 80%. B-: The film strength was 55% or more and less than 65%. C: The film strength was less than 55%.

[0128] (ink absorbency) Using an inkjet recording device (product name "imagePROGRAF Pro4000", manufactured by Canon) equipped with a water-based pigment ink (cyan ink), a solid image was recorded on the recording medium with the print mode set to "standard mode for waterproof poster synthetic paper." The ink was then visually observed for drying immediately after printing and for overflow of the ink in the resulting image, and the ink absorbency was evaluated according to the following evaluation criteria. The images were printed under conditions of a temperature of 23°C and a humidity of 50%. It was confirmed that the coloring material of the ink used was a pigment with an average particle size of 50 nm to 180 nm. A: The ink dried very well immediately after printing, and there was absolutely no overflow. B: The ink dried slightly less immediately after printing, but there was almost no overflow. C: The ink was not dried properly immediately after printing, and overflow was observed.

[0129] TIFF0007631114000007.tif129170

Claims

1. A recording medium having a substrate, an ink receiving layer (1) provided on the substrate, and an ink receiving layer (2) provided on the ink receiving layer (1) and disposed on the outermost surface thereof, The thickness of the ink receiving layer (2) is 10 nm or more and 4,000 nm or less, The ink receiving layer (1) contains first inorganic particles and a first binder, the ink receiving layer (2) contains second inorganic particles and a second binder, The first binder and the second binder are both water-insoluble resins, a contact angle θ1 between the surface of the ink receiving layer (1) and water one second after the surface of the ink receiving layer (1) is brought into contact with water is 90° or more; A recording medium characterized in that the contact angle θ2 of the surface of the ink receiving layer (2) with water one second after the surface of the ink receiving layer (2) is brought into contact with water is 60° or more and 85° or less.

2. The recording medium according to claim 1 , wherein the contact angle θ1 and the contact angle θ2 satisfy the relationship of the following formula (1). θ1-θ2≧10°...(1)

3. A recording medium having a substrate, an ink receiving layer (1) provided on the substrate, and an ink receiving layer (2) provided on the ink receiving layer (1) and disposed on the outermost surface thereof, The thickness of the ink receiving layer (2) is 10 nm or more and 4,000 nm or less, The ink receiving layer (1) contains first inorganic particles and a first binder, the ink receiving layer (2) contains second inorganic particles and a second binder, The first binder and the second binder are both water-insoluble resins, a contact angle θA of the surface of the ink receiving layer (2) with water 60 seconds after the surface of the ink receiving layer (2) is brought into contact with water is 40° or more and 80° or less; A recording medium characterized in that a contact angle θA' of the surface of the ink receiving layer (2) with water 60 seconds after the recording medium is immersed in water for 60 minutes and then thoroughly dried and the contact angle θA satisfies the relationship of the following formula (I). θA'-θA≧5°...(I)

4. 4. The recording medium according to claim 1, wherein the ink receiving layer (2) has a thickness of 10 nm or more and 500 nm or less.

5. A recording medium described in any one of claims 1 to 3, wherein the thickness of the ink receiving layer (2) is 10 nm or more and 300 nm or less.

6. 6. The recording medium according to claim 1, wherein the first inorganic particles are at least one type selected from the group consisting of alumina hydrate, fumed alumina, and fumed silica.

7. The recording medium described in claim 6, wherein the first inorganic particles are alumina hydrate and have an average primary particle size of 20 nm or more and 100 nm or less.

8. 8. The recording medium according to claim 1, wherein the ink receiving layer (1) contains 14% by mass or less of a first water-soluble resin based on the content of the first binder in the ink receiving layer (1), or does not contain the first water-soluble resin.

9. 9. The recording medium according to claim 1, wherein the ink receiving layer (2) contains 14% by mass or less of a second water-soluble resin based on the content of the second binder in the ink receiving layer (2), or does not contain the second water-soluble resin.

10. a mass ratio of the content of the second binder to the content of the second inorganic particles in the ink receiving layer (2) is 10. The recording medium according to claim 1, wherein the mass ratio of the first binder to the content of the first inorganic particles in the ink receiving layer (1) is lower than that of the first binder.

11. 11. The recording medium according to claim 1, wherein the water-insoluble resin is at least one selected from the group consisting of an acrylic resin, a polycarbonate-modified urethane resin, and a polyether-modified urethane resin.

12. The first binder is at least one selected from the group consisting of an acrylic resin, a polycarbonate-modified urethane resin, and a polyether-modified urethane resin; 12. The recording medium according to claim 1, wherein the second binder is an acrylic resin.

13. 13. The recording medium according to claim 1, wherein the second inorganic particles are colloidal silica.

14. The recording medium according to claim 13, wherein the colloidal silica is cationic colloidal silica.

15. A recording medium described in any one of claims 1 to 14, wherein the ink receiving layer (2) contains a surfactant.

16. The recording medium according to claim 15, wherein the surfactant is an acetylene-based surfactant.

17. The recording medium according to claim 16, wherein the acetylene-based surfactant is acetylene glycol.

18. A recording medium described in any one of claims 15 to 17, wherein the HLB value of the surfactant is 13 or more and 17 or less.

19. The recording medium according to any one of claims 1 to 18, which is for inkjet use.

20. An inkjet recording method for recording an image on a recording medium by ejecting ink from an inkjet recording head, comprising: the ink is a water-based ink containing a pigment, 20. An ink jet recording method, comprising the recording medium according to claim 1.

Citation Information

Patent Citations

  • Recording sheet

    JP2002002090A

  • Liquid composition and recording medium

    JP2006051741A

  • Inkjet recording medium, its manufacturing method and recording method employing the same

    JP2006110787A

  • Ink-jet recording material

    JP2008105235A

  • Recording medium

    JP2015030242A